Fairness in sovereign debt restructuring - Christian Engelen; Johann Graf Lambsdorff (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2007)
Experience from events of sovereign debt restructuring over the last decade exemplifies that the prevailing process is mainly shaped by exchange-offer launched by the debtor. This suggests that negotiations for changing the repayment terms of the debt take place in an Ultimatum Game which centres virtually the whole bargaining power on the debtor side. Creditors vote according to reservations values that might be influenced by fairness consideration both vis-à-vis the debtor and their fellow creditors. And as fairness is usually a highly subjective influence this can result heterogeneity of reservation values which might impede effective intra-creditor coordination for the benefit of the debtor.
Keywords: 330